Nickel(II) complexes bearing pyrazolylpyridines: synthesis, structures and ethylene oligomerization reactions. (16th November 2015) - Nyamato, George S.; Alam, Mohd. Gulfam; Ojwach, Stephen O.; Akerman, Matthew P.
Abstract : Reactions of 2‐bromo‐6‐(3, 5‐dimethyl‐1 H ‐pyrazol‐1‐yl)pyridine (L1 ) and 2, 6‐bis(3, 5‐dimethyl‐1 H ‐pyrazol‐1‐yl)pyridine (L2 ) with NiCl2 and NiBr2 led to the formation of their respective metal complexes [NiCl2 (L1)] (1 ), [NiBr2 (L1)] (2 ) and [NiBr2 (L2)] (3 ) in moderate to high yields. The complexes were characterized using elemental analyses, mass spectrometry and single‐crystal X‐ray diffraction for2 . The solid‐state structure of2 confirmed the bidentate coordination mode ofL1 and formation of a monometallic compound. Activation of the nickel(II) pre‐catalysts with methylaluminoxane afforded active catalysts in the ethyleneoligomerization reaction to produce mainly butenes (84–86%). In contrast, activation of nickel(II) pre‐catalyst2 with ethylaluminium dichloride resulted in partialFriedel–Crafts alkylation of the toluene solvent by the preformed oligomers. Complex structure, nature of co‐catalyst employed, type of solvent and reaction conditions influenced the catalytic behaviour of these pre‐catalysts. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Activation of (pyrazolyl)pyridine nickel(II) complexes with methylaluminoxane (MAO) in toluene solvent resulted in the formation of active catalysts to afford C4, C6 and C8 products as well as minimal amounts of ethylene‐alkylated toluene, while activation with EtAlCl2 in toluene produced mainly Friedel–Crafts alkylated products together with some amount of C4 and C6 oligomers. Reactions in chlorobenzene yielded only C4 and C6 oligomers.